Partial Obstruction and Intestinal Bleeding Secondary to a Congenital Duodenal Diverticulum in a Dog - Lorigados, Carla Aparecida Batista; Zoppa, Aline Machado; Schiller, Andre; Tiburcio, Iara; Calderon, Fabio Giusti; Pantano, Marianna (Acta Scientiae Veterinariae, 2021)
Background: Intestinal diverticulum is an abnormality resulting in the formation of a blind-ended saccular pouch that can be acquired either congenital, true (involving all intestinal layers) or false (involving the mucosa and submucosa), with extraluminal and intraluminal type. In humans, the acquired is more frequent, being the colon is the most affected segment followed by duodenum; most of duodenal diverticulum remains asymptomatic, but biliary obstruction, recurrent acute pancreatitis, hemorrhagic ulcer, proximal intestinal obstruction and perforation may occur. The aim of this report is to present a case of a congenital disease in dogs, prone to misdiagnosis due to non-specific clinical signs. Case: An 8-month-old male Boxer was evaluated due to recurrent hyporexia, vomiting, melena and syncope over three months with signs of a possible intestinal obstruction. Physical examination showed no abnormalities except for pale mucous membranes. Complete blood count revealed anemia and leukocytosis. Platelets and biochemical profiles were normal. Abdominal ultrasound examination indicated a dilated duodenum, measuring approximately 3.36 cm in diameter, with heterogeneous fluid content and hyperechogenic structures with acoustic shadow, peristalsis appeared decreased and non-progressive. The gastrointestinal positive contrast study was performed to better evaluate abnormalities detected at ultrasonography. Images after 30 m of contrast administration demonstrated a marked distension of the duodenum, filled with contrast and a mildly filled stomach displaced to the left. Sixty min after contrast administration a marked distension of the entire duodenum, with tortuous aspect and filled with contrast was seen. The caudal duodenal flexure was connected to a large barium filled saccular structure that measured approximately 7 cm in diameter, consistent with a duodenal diverticulum. A blood transfusion was performed and surgical treatment indicated. The diverticulum and a small portion of the caudal duodenal segment were resected, an end-side enteroanastomosis was made due to the difference in diameter between intestinal segments. The patient was medicated with sucralfate (12.5 mg/kg), ranitidine (2 mg/kg), metronidazole (25 mg/kg), dipyrone (25 mg/kg) and, tramadol (2 mg/kg) and recovered quickly from surgery. Histopathological examination characterized the diverticular tissue as a true diverticulum by the presence of all intestinal layers. Post-operative and follow-up evaluations showed no recurrence of clinical signs. Discussion: In veterinary practice, congenital duodenal diverticulum is a rare condition documented in dogs, curiously all Boxers None of the reported cases in literature had the diagnostic of duodenal diverticulum made exclusively by ultrasonography. Other diagnostic imaging modalities, such as gastrointestinal barium study or endoscopy, were necessary. In one case a diagnostic was made during exploratory laparotomy. The marked dilatation of the duodenal segment impaired ultrasound evaluation, allowing recognition of an obstructive pattern, not the diverticulum itself. At histopathological examination, the diverticular tissue was characterized by a thickened wall with a hypertrophied muscle layer, characterizing a true duodenal diverticulum. The location, breed and age of the dogs affected with duodenal diverticulum was similar in all veterinary cases reported. Dogs presenting signs of gastrointestinal disease and abdominal pain are common in patients referred to ultrasound examination. However, despite the rare reports described, we must consider this affection as a differential diagnosis, whenever boxer puppies present these clinical signs associated with gastrointestinal bleeding and syncope.